Characteristics associated with post-pandemic nutritional status in schoolchildren from an educational institution in Huánuco, Peru - Céspedes-Espinoza, Jhenifer Carmen (2024)
Objective. To determine the relationship between general characteristics and post-pandemicnutritional status in schoolchildren from an educational institution in Huánuco, Peru. Methods. A quantitative, descriptive, cross-sectional study with a comparative descriptive design. The population consisted of 228 students, and the sample included 143 students, to whom a validated questionnaire and a registration form were applied. Fisher's exact test and Kendall's Tau-b were used for inferential analysis. Results. It was found that 25.2% (36) of the students were overweight and 3.5% (5) were obese. A significant relationship was also found between the frequency of food consumption and nutritional status (p-value = 0.001). Conclusion. It is concluded that there is a signifcant relationship between the frequency of food consumption and the nutritional status of schoolchildren.